Degree of tinnitus improvement with stapes surgery - a review - Cavalcante,Aliciane Mota G. (2018)
Abstract Introduction Otospongiosis is temporal bone osteodystrophy, characterized by disordered bone resorption and neoformation in genetically predisposed individuals. Clinically, otospongiosis is characterized by progressive conductive and/or mixed hearing loss and by tinnitus. Objective A review of the last two decades of publications that report the degree of tinnitus improvement with stapes surgery. Methods 125 articles published in the last 20 years mentioning the relationship between otosclerosis and tinnitus. Literature has always shown that the hearing improvement after stapes surgery was the main result sought and found. However, recent articles has reinforced the need for surgery for the tinnitus improvement. The ideal time to assess tinnitus through different scales is in the sixth month post-operative. The estimated average hearing improvement is 93% and tinnitus is 85.52%. Results Summaries of 12 articles were reviewed which fulfilled the search criteria of the survey, and 8 studies were included in the study according the selection criteria. This studies investigating the degree of tinnitus improvement with stapes surgery, using different scales as: tinnitus functional index, visual analog scale, tinnitus functional index and visual analog scale, visual analog scale and "questionnaire asking about tinnitus", Newman's method and Tinnitus Score Advocated by the Japan Audiological Society. The total of the samples of the evaluated articles was of 254 participants. Conclusion We conclude that stapes surgery is effective for the treatment of tinnitus (average improvement is 85.52%), and hearing loss (average improvement is 93%). When deciding about the surgical indication in patients with otosclerosis, the presence and level tinnitus should be considered as well as the level of hearing.